The Effect of Employee Adaptation and Government Capacity on the Success of the Regional Government Information System (SIPD) - Fauzia, Melia; Surahman, Nabilah Putri; Rizki, Mhd. Nanda; Laia, Tri Putrianis; Irawan (CV Raskha Media Group, 2025)
This study aims to formulate a conceptual model that explains the influence of employee adaptation and government capacity on the success of implementing the Regional Government Information System (SIPD). The main issues identified include uneven levels of employee adaptation to digital system changes, limited technical and managerial competencies among public officials, and institutional capacity constraints within local governments that do not yet fully support the optimal utilization of SIPD. In addition, a gap remains between the intended objectives of SIPD implementation as an instrument for integrating regional planning and financial management and the realities of its operational execution. To address these issues, this study employs a conceptual–exploratory research design using a conceptual modeling approach and content analysis, strengthened by a comprehensive literature review, analysis of regulations related to SIPD, and synthesis of recent research findings in the field of e-government and public sector information systems. The analytical techniques include identifying dimensions of employee adaptation, evaluating government capacity encompassing human resources, institutional arrangements, and technological support, as well as conducting gap analysis to formulate the key determinants of SIPD success. The expected outcome of this study is a conceptual model that illustrates the logical relationships between employee adaptation, government capacity, and SIPD success, which can serve as a foundation for policy formulation aimed at enhancing public sector capabilities and strengthening digital governance in local governments.